Private Interhousehold Transfers in Vietnam in the Early and Late 1990s - Cox, Donald (World Bank, Washington, D.C., 2013)
The author uses date from the 1992-93 and 1997-98 Vietnam Living Standards Survey (VLSS) to describe patterns of money transfers between households. Rapid economic growth during the 1990s did little to diminish the importance of private transfers in Vietnam. Private transfers are large and widespread in both surveys, and are much larger than public transfers. Private transfers appear to function like means-tested public transfers, flowing from better-off to worse-off households and providing old age support in retirement. Panel evidence suggests some hysteresis in private transfer patterns, but many households also changed from recipients to givers and vice versa between surveys. Changes in private transfers appear responsive to changes in household pre-transfer income, demographic changes, and life-course events. Transfer inflows rise upon retirement and widowhood, for example, and are positively associated with increases in health expenditures. It also appears that private transfer inflows increased for households affected by Typhoon Linda, which devastated Vietnam's southernmost provinces in late 1997.